2016
DOI: 10.3109/02713683.2015.1116585
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatic Peripheral Defocus with Different Contact Lenses: Review and Meta-Analysis

Abstract: Orthokeratology, multifocal soft CL, and custom-designed RGP CL were able to generate a significant relative peripheral myopia in myopic eyes. Conversely, standard and experimental soft CL were not able to induce significant peripheral myopic and astigmatic defocus values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…However, the changes in refraction occurred more quickly into the nasal field than into the temporal field. This is consistent with previous studies, and will be investigated further.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the changes in refraction occurred more quickly into the nasal field than into the temporal field. This is consistent with previous studies, and will be investigated further.…”
Section: Discussionsupporting
confidence: 93%
“…The peripheral zones of multifocal contact lenses are rotationally symmetrical. However with multifocal contact lenses, studies have found more myopic shift on peripheral refraction for the nasal than for the temporal visual field …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, several optical means have attempted to reduce the magnitude of hyperopic peripheral defocus or peripherally impose myopic defocus while maintaining good correction of foveal refractive errors. Orthokeratology, multifocal soft contact lenses, custom-designed rigid gas permeable lenses, and some novel contact lens designs can effectively regulate peripheral refraction in myopic eyes [9][10][11]. If the hypothesis is correct, it is important to quantify the effect of these lenses on imposing peripheral myopic defocus.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed to slow myopia progression; among them, non-pharmacological treatments, like orthokeratology and peripheral defocus modifying contact lenses (CLs) achieved very good outcomes, which has been attributed to the induction of a myopic Relative Peripheral Refractive Error (RPRE), although the optical mechanisms for myopia development still remain controversial. [1][2][3][4][5][6][7] Different designs of multifocal CLs were proposed to this aim, 6,[8][9][10] and consequently, the amount and extension of the induced RPRE vary among lenses. Since the ocular growth during the emmetropization process might depend on the stimulated retinal areas, 11 it is expected that different designs will provide different results.…”
Section: Introductionmentioning
confidence: 99%